2019
DOI: 10.1038/s41598-019-44865-1
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miRNA-25-3p inhibits Notch1 signaling and TGF-β-induced collagen expression in hepatic stellate cells

Abstract: During chronic liver injury hepatic stellate cells (HSCs), the principal source of extracellular matrix in the fibrotic liver, transdifferentiate into pro-fibrotic myofibroblast-like cells - a process potentially regulated by microRNAs (miRNAs). Recently, we found serum miRNA-25-3p (miR-25) levels were upregulated in children with Cystic Fibrosis (CF) without liver disease, compared to children with CF-associated liver disease and healthy individuals. Here we examine the role of miR-25 in HSC biology. MiR-25 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 74 publications
(84 reference statements)
2
16
0
Order By: Relevance
“…The dose-related fold increase over that of the control was exceptional. The large increase in miRNA levels after transfection was consistent with recent literature 19 , 20 . When transfecting the inhibitors, the target miRNAs were detected to be near zero, indicating the successful inhibition of the miRNAs of interest using their inhibitors.…”
Section: Resultssupporting
confidence: 92%
“…The dose-related fold increase over that of the control was exceptional. The large increase in miRNA levels after transfection was consistent with recent literature 19 , 20 . When transfecting the inhibitors, the target miRNAs were detected to be near zero, indicating the successful inhibition of the miRNAs of interest using their inhibitors.…”
Section: Resultssupporting
confidence: 92%
“…In a very recent study, we could demonstrate that profibrogenic effects of miR-942 are mediated through targeting BAMBI, a TGF-β decoy receptor, leading to enhanced fibrogenic TGF-β signaling [176]. Further, Genz et al showed an antifibrotic role for miR-25-3p, mediated by its ability to inhibit TGF-β induced SMAD2 phosphorylation and collagen deposition in LX-2 cells [186].…”
Section: Tgf-β Signaling and Epigenetics In Liver Fibrosismentioning
confidence: 99%
“…miRNAs are involved in almost all physiological and pathological events, including the fine regulation of the Notch pathway. Indeed, an ever-growing number of miRNAs have been reported as modulators of the Notch pathway [ 40 43 ]. A list of miRNAs experimentally-validated by gene reporter assay as negative regulators of Notch receptors and ligands is available as Supplementary Information [see Additional file 1 : Table S1].…”
Section: Notch Activation Processing and Regulationmentioning
confidence: 99%